Organic and inorganic fertilizer application enhances the effect of Bradyrhizobium on nodulation and yield of peanut (Arachis hypogea L.) in nutrient depleted and sandy soils of Ethiopia - Anteneh Argaw (International Journal of Recycling of Organic Waste in Agriculture)
Abstract Purpose An investigation was carried out to evaluate the effect of the integrated application of organic and inorganic fertilizer effect on Bradyrhizobium effectiveness on nodulation and yield of peanut at the major growing areas of Eastern Ethiopia, Babillae and Fedis sites. Methods Systemic combination of compost, manure, Bradyrhizobium inoculation and NP application was laid out in Randomized Complete Block Design with three replications. Results The result showed that Bradyrhizobium integrated with organic inputs significantly improved the nodule number at Babillae while Bradyrhizobium when applied with DAP resulted in a significant increase of nodulation at Fedis site. The highest total biomass and total pods weight at both sites were found to record when Bradyrhizobium integrated with manure and compost. Integration of Bradyrhizobium, manure and compost at Fedis and Bradyrhizobium with manure at Babillae was found to increase the kernel yield by 44 and 66.6% over the control check, respectively. Integration of Bradyrhizobium, manure and compost at Babillae and Bradyrhizobium with starter N at Fedis significantly increased plant N accumulation. The effect of organic and inorganic application on soil N and organic carbon content was not significant at Fedis, but the slight increase was observed in Babillae site. A significant increase in the soil available P by organic and/or DAP application was found in either of the experimental sites. Conclusion Organic fertilizer when integrated with Starter N and DAP is better in improving the effectiveness of Bradyrhizobium, nodulation and yield of peanut in either of the sites.